Prediagnostic Level of Serum Retinol in Relation to Reduced Risk of Hepatocellular Carcinoma - Jian‐Min Yuan; Yu‐Tang Gao; Choon Nam Ong; Ronald K. Ross; Mimi C. Yu (2006)
Retinol and its derivatives (retinoids), which have antioxidant activity and promote cell differentiation, may protect against the development of hepatocellular carcinoma (HCC) by controlling hepatocellular differentiation and reducing inflammatory responses.We examined prospectively the relationship between prediagnostic serum concentrations of retinol, alpha-carotene; beta-carotene; beta-cryptoxanthin; lutein; lycopene; zeaxanthin; alpha-, gamma-, and delta-tocopherols; and selenium and the risk of developing HCC among 213 patients with HCC and 1087 matched control subjects from a cohort of 18,244 men in Shanghai, China, who were monitored from 1986 through 2001. Odds ratios (ORs) and 95% confidence intervals (CIs) for men by quartile of serum concentrations of micronutrients were estimated by using logistic regression with adjustment for cigarette smoking status, alcohol intake, self-reported history of physician-diagnosed hepatitis or liver cirrhosis at recruitment, and seropositivity for hepatitis B surface antigen (HBsAg). All statistical tests were two-sided.Men with high prediagnostic serum retinol levels had a lower risk of HCC than men in the lowest quartile (Q2 versus Q1, OR = 0.37, 95% CI = 0.22 to 0.61; Q3 versus Q1, OR = 0.30, 95% CI = 0.17 to 0.50; and Q4 versus Q1, OR = 0.13, 95% CI = 0.06 to 0.26; Ptrend < .001). A statistically significant interaction was observed between retinol and HBsAg seropositivity on HCC risk; HBsAg-positive men in the lowest tertile of retinol had a greater than 70-fold higher risk (OR = 72.7, 95% CI = 31.6 to 167.4) of HCC than HBsAg-negative men in the highest tertile of retinol (Pinteraction = .018). No independent effect of serum levels of alpha-carotene; beta-carotene; beta-cryptoxanthin; lutein; lycopene; zeaxanthin; alpha-, gamma-, and delta-tocopherols; or selenium on HCC risk were observed.High prediagnostic serum level of retinol is associated with a decreased risk of HCC in this population.